Factors influencing choice of strategic management modes of small enterprises - Nyangara Charles; Patrick B. Ojera; Oima David (Journal of Innovation and Entrepreneurship, 2015)
Studies indicate that 75% of small enterprises in the world fail during their first 5 years of operation. In Kenya, just about 20% grow to the next size category. Scholars have prescribed formal strategic management modes, but the small enterprises (SEs) continue to not only fail but also depict informal strategic management modes. However, few studies have been done to examine whether the dismal performance of SEs is due to other factors unrelated to the management of the enterprises, especially in the context of a developing country like Kenya. The specific objectives were to identify the strategic management modes employed by the small enterprises in Kisumu County with specific reference to the Youth Enterprise Fund beneficiaries in Kisumu County and to assess the factors influencing the choice of these modes. The study was anchored on Mintzbergs' theories on deliberate, emergent, and reactive strategic management modes. The study adopted a descriptive cross-sectional research design. The target population was the 242 small enterprises run by the Youth Enterprise Development Fund (YEDF), out of which 134 enterprises were sampled using Yamane's criteria. The study adopted questionnaire and interview methods as the basic data collection methods with the questionnaire being tested through content validity index and Cronbach alpha's internal consistency index, respectively. The study found that the basic modes used by small enterprise were deliberate, emergent, and reactive and that the small enterprises in Kisumu County used these modes interchangeably but relied more on the reactive mode of strategic management. The study revealed that the choice of these modes was dictated by the personal, environmental, and firm characteristics of the enterprises. The study concludes that continued exposure to formal modes would only sustain the endemic failure of the SEs because the SEs need formal exposure to models that address their situation. The study therefore urgently recommends formalization of elements of reactive strategic management modes and the personal factors in small firm curricula.
Keywords: 650; Informal strategic management; Deliberate strategic management mode; Emergent strategic management; Reactive strategic management